Book Review: Sisson (2024). Relinquished: The Politics of Adoption and the Privilege of American Motherhood. New York: St. Martin’s Press. ISBN: 978-1250286772 - Marianne Novy (Genealogy)
A larger proportion of women in the United States than in any other developed country—though less than 1 per cent—relinquish infants for adoption [...]